The results of the “Blue Cards” questionnaire analysis with respect to the incidence of violence among the elderly - Giezek, Marta; Bażydło, Marta; Ciechowicz, Jacek; Masna, Barbara; Zabielska, Paulina; Tomczak, Joanna; Paszkiewicz, Monika; Safranow, Krzysztof; Karakiewicz, Beata (Family Medicine & Primary Care Review, 2017)
Background. Implementation of the “Blue Cards” procedure has resulted in an increase in reported acts of violence, including those concerning the elderly, not because violence has become more widespread, but because the principles of the fight against domestic violence have been established and competencies of the relevant services have been distributed. Objectives. The aim of the study is to review the “Blue Cards” questionnaires of people over the age of 60 involved in domestic violence. Material and methods . The study involved 1,299 “Blue Cards” questionnaires, which were obtained in the years 2012–2013 by the Interdisciplinary Team dealing with domestic violence prevention in Szczecin. From this sample, 312 forms obtained from individuals above the age of 60 were analyzed. Results . Elderly people are involved in violence in three ways: as individuals experiencing violence, as those who use violence or as individuals who witnesses violence. Without a doubt, the majority of people who are affected by violence are women who are harmed by their husbands. Domestic violence amongst elderly people is usually disclosed after 1–3 years of its duration; however, it occasionally happens after more than 7 years. The dominant emotion in victims of domestic violence is fear, and in perpetrators – aggression. Conclusions . There are still many cases of domestic violence amongst people over 60 years of age that remain undisclosed, hence co-operation amongst services is extremely important, as well as continuously raising the competence of police officers, education, social assistance and health care specialists. The aim is to counteract violence amongst the elderly and to restore balance to their daily functioning.